Alevi, Kizilbas or Shia? Some New Thoughts on the Usage of the Word “Alevi” Through History with its Current Sense - Akın, Bülent (Journal of Alevism-Bektashism Studies, 2023)
The word of “Alevi” has been used in the meanings of “Ali supporters”, “Ali descendants” or “descendants of the Prophet, sayyids” in the historical process made the most of the researchers believed that this word was not used to name the communities called Kalenderi, Haydari, Cavlaki, Işık, Torlak, Abdal, Rafizi, Kızılbaş or Bektashi before the 19th century. Alevi communities’ devotion to Ali and Ehl-i Beyt, their love for the Twelvers, and their sensitivity to the Karbala caused that they have been evaluated in the Shia belief system. However, as can be seen in the determinations in this article, it is clearly seen in historical sources that the word “Alevi” is an umbrella concept and nomenclature that covers all of these namings, just like the naming of “Kızılbaş”. The afore-mentioned sources show that, contrary to the opinions up to now, the use of the word “Alevi” in its current sense is not a usage of the last few centuries and the history of this naming can be traced back to 15th century. In addition, there is a lot of evidence pointing out that Alevism has existed with different characteristics from Shia throughout history. In this context, in the article, the question of “How long the word ‘Alevi’ has been used as an umbrella concept for the Kızılbaş communities, defined by researchers as heterodox Islam, in the historical process?” has been discussed by using written sources belonging to both believers and non-believers. In addition, findings that Alevism has an independent existence from Shia belief in terms of both its formation in the historical process and its theology and doctrine are discussed. We believe that these findings will contribute to the review of the conceptual framework of the word “Alevi” in the historical process and to understand the historic structure of the social and faith-based organizations, especially the Ocak system, of the communities belonging to this belief.In this context, the sources used in the article, the methods followed and the conclusions reached can be summarized as follows: Until recently, the term “guruh-ı alevi” in the Hatt-ı Hümayun (dated September 2, 1826) regarding the closure of the Rumeli Bektashi lodges during the reign of Mahmud II, was accepted as the first used with the same meaning as today’s Alevi/Kızılbaş term in written sources. However it has been determined that the word “Alevi” is used to describe both the Alevi belief, which has a Ocak-centered structure, in its current meaning and Kızılbaş in the land registry records belonging to the Ordu province dated to 1455, 1485, 1553 and 1579, and Celalzâde Salih Çelebi’s work named Tarih-i Sultan Süleyman which was written in 1528, and the couplets in Divans of 16th century poets Aşkî and Hayalî Bey and included in the work of Âşık Çelebi named Meşâ‘irü’ş-Şu‘arâ.Additionally, in the article, there are some new findings and opinions contrary to the recent studies on the relationship of Alevism and Shiism. These findings and opinions can be listed as follows: In the light of the newly identified poems of Cihanşah Hakiki and the information included in the land registry records clearly show that the basic terminology of Alevism was formed and used proficiently before the 16th century. Since the 15th century, the term Alevi has been included in the written sources in a way that includes the Ocaks and Kızılbaş with its current meaning, and the person names in the land registry records of these centuries coincide with the basic belief and ritual world of the Alevi faith. Poets who define themselves as “Kalenderi, Haydari, Işık, Torlak, Abdal, Kızılbaş”, used the term Alevi as a meta-name covering these names in their poems, and the sources mentioning these poets also used the same nomenclature. All these findings, together with the determinations on the religious structure of the Safavids, show that Alevism is a belief system that emerged and survived independently of Shia.In the article, it has been also questioned and discussed whether the word “Kızılbaş” was used and became widespread earlier than the term “Alevi”. The fact that Ordu, where the Çepnis settled, was registered as “Bölük-i Niyabet-i Ordu bi-ismi Alevî” in the cadastral registers written in 1455 and it was named as “Bölük-i Niyabet-i Ordu nam-ı diğer Alevi” in the cadastral registers written in 1485 shows that the term “Alevi” was used earlier than the word “Kızılbaş” which was started to be used as a political and military term by Şeyh Haydar (b. 1459-60 - d. 1488), son of Şeyh Cüneyd, and became widespread enough to be recorded in official documents. As a matter of fact, it will be clearly seen that the word “Alevi” is more likely to be older than the word “Kızılbaş” in describing these communities, considering that the land registry records in which the word Alevi is used in today’s sense of Alevism, were first written in 1455, that is 5 years before the birth of Şeyh Haydar. It shows that Alevism, which has a sufistic structure in terms of theology and doctrine, started to become politicized after the Safavid sheiks Şeyh Cüneyd and his son Şeyh Haydar, and that the word “Kızılbaş” was preferred by Şeyh Haydar within this context. Likewise, the political and military steps taken by the the above-mentioned Safavid sheiks and later Şah Ismail, confirm this thesis. Additionally, in the texts of the 16th century included in the article, the use of the term Alevi together with the “semâ/semah” ritual, contrary to the word Kızılbaş, is another remarkable issue that confirms our thesis.
Keywords: Alevi; Kizilbash; Şia; Kalenderi; heterodox; naming